Tandem mass spectrometry of intact GroEL-substrate complexes reveals substrate-specific conformational changes in the trans ring. - van Duijn, E; Simmons, D; van den Heuvel, R; Bakkes, P; van Heerikhuizen, H; Heeren, R; Robinson, C; van der Vies, S; Heck, A (2006)
It has been suggested that the bacterial GroEL chaperonin accommodates only one substrate at any given time, due to conformational changes to both the cis and trans ring that are induced upon substrate binding. Using electrospray ionization mass spectrometry, we show that indeed GroEL binds only one molecule of the model substrate Rubisco. In contrast, the capsid protein of bacteriophage T4, a natural GroEL substrate, can occupy both rings simultaneously. As these substrates are of similar size, the data indicate that each substrate induces distinct conformational changes in the GroEL chaperonin. The distinctive binding behavior of Rubisco and the capsid protein was further investigated using tandem mass spectrometry on the intact 800-914 kDa GroEL-substrate complexes. Our data suggest that even in the gas phase the substrates remain bound inside the GroEL cavity. The analysis revealed further that binding of Rubisco to the GroEL oligomer stabilizes the chaperonin complex significantly, whereas binding of one capsid protein did not have the same effect. However, addition of a second capsid protein molecule to GroEL resulted in a similar stabilizing effect to that obtained after the binding of a single Rubisco. On the basis of the stoichiometry of the GroEL chaperonin-substrate complex and the dissociation behavior of the two different substrates, we hypothesize that the binding of a single capsid polypeptide does not induce significant conformational changes in the GroEL trans ring, and hence the unoccupied GroEL ring remains accessible for a second capsid molecule.